Resistance element welding of magnesium alloy and austenitic stainless steel in three-sheet configurations - Manladan, Sunusi Marwana; Zhang, Y.; Ramesh, Singh; Cai, Yang Chuan; Ao, Sansan; Luo, Zhen (Elsevier, 2019)
The Mg alloy and two austenitic stainless steel sheets were joined together by a metallurgical bond across the rivet and two austenitic stainless steel sheets. More heat was generated at the austenitic stainless/austenitic stainless interface than at the rivet/ austenitic stainless steel interface, leading to larger nugget size at the austenitic stainless steel /austenitic stainless steel interface at all welding currents. Thus, the nugget size at the austenitic stainless steel /austenitic stainless steel interface mainly influenced the transition from interfacial to pullout failure modes. The fusion zone microstructure consisted of ferrite and austenite. The microstructure in the edges of the nugget (both in the rivet and ASS) consisted of fine columnar dendritic grains. Owing to variation of temperature gradient and solidification growth rate, the grains morphology changed from columnar dendritic to equiaxed dendritic in the nugget center. The fine grains resulted in high fusion zone hardness. Digital image correlation analysis revealed that the joints could experience joining zone rotation/out-of-plane displacement during lap-shear tests, which reduced the magnitude of strain sustained by the joints in the loading direction. The joint configuration that did not undergo joining zone rotation and failed via pullout failure in the austenitic stainless steel sheet exhibited superior lap-shear performance. © 2019